Pengaruh Pembelajaran Matematika dengan Menggunakan Media Video Pembelajaran terhadap Motivasi Belajar Matematika Siswa SMPN 2 Baubau - Fita Fita; Dian Lestari (Program Studi Pendidikan Matematika, Fakultas Keguruan dan Ilmu Pendidikan, Universitas Dayanu Ikhsanuddin, 2022)
The formulation of the problem in this study is whether there is an effect of learning mathematics by using mathematics learning videos on the motivation of learning mahematics in seventh grade student of SMPN 2 Baubau. The purpose of this study was to determine whether there was an effect of learning mathematics by using learning videosi on the motivation to learn mathematics in class VII students of SMP Negeri 2 Baubau.This research is a guantitative research with a quasi-experimental design method. The population in this study were all grade VII students of SMP Negeri 2 Baubau in the odd semester of the 2022/2023 academic year whiich consisted of 9 class and the samples used were clas VII.8 and VII.9, totaling 58 student using cluster random samplinh technique. Collecting data in this study used a questionnaire on students’ motivation to learn mathematics. The data obtained were analyzed using the Independent Sample T-Test.Based on the result of the study, it was conculuded that the tcount value was 3,43 and ttable value was 2,003 at a significant level of 5% with df 56. Thus, the tcount > ttable, then H0 was rejected. So, it can be concluded that learninmg mathematics by using learning videos has a significant positive effect on Mathematics Learning Motivation of Class VII students of SMP Negeri 2 Baubau.